JAIKISAN: An Interface For Telugu Farmer - Srilekha, S; Navya Sri, P; SriSagar, G; S. V. S. Sridhar, P (International Journal of Engineering and Technology, 2018)
An Indian farmer is one of the important members of society. The farmer has many kinds of work to do in the fields. Agriculturists furrow their fields. They sow the seeds, waters the fields frequently. They should be careful with the products. They have conjointly to sprinkle pesticides in the fields. Farmers basically depend on the rain. Sometimes rainfall will occur according to the season but sometimes no rainfall or very less rainfall and sometimes floods may occur damaging all crops and consequently great losses for farmers. Now we have decided to develop an interface in Telugu language, where farmers can easily find solutions to their problems. Interface helps the Agriculturists to get the information regarding rainfall, types of crops suitable for that particular land. Besides, we will also provide some related videos and expert advisors. The consumer can find their required information, queries through the interface. They receive supposed statistics, associated videos. The interface helps the Agriculturists to get the information regarding rainfall, types of crops suitable for that particular land. Â Â